Analisis Faktor-faktor yang Mempengaruhi Pendapatan Usaha Tani Jeruk Siam (Studi pada Petani Jeruk Siam di Kecamatan Besitang, Kabupaten Langkat, Sumatera Utara) - Rias Tampani Lubis; Rahmanta; Tavi Supriana (Nomicpedia: Journal of Economics and Business Innovation, 2021)
Citrus is a horticultural commodity that is feasible to develop because citrus farming provides high profits, so it can be used as a source of income for farmers. The formulation of the problem of this research is the marketing channels and what factors affect the income of farmers in Besitang District, Langkat Regency. By using descriptive and quantitative methods of secondary data samples and primary data taken directly from farmers and traders with a total population of 46 which is proportional to 36 farmers, 5 agents, and 5 retailers. The test is carried out with the F-test for simultaneous and the t-test for partial testing. The results showed that there were only two marketing channels, namely the first level channel (one level channel) and the second level channel (two-level channel) with a margin of 62.19% between farmers and agents while 27.81% between agents and retailers, then production. , price, capital, land rent, and labor wages simultaneously affect the income of farmers, and partially the production, price, and capital variables have an influence on farmers' income but partially there is no effect between land rent and labor wages on the income of citrus farmers. Siam in Besitang District, Langkat Regency.